Association Analysis of Complications, Number of Drugs, and Medication Adherence in End-Stage Renal Disease Patients Undergoing Hemodialysis - Ratnasari, Pande Made Desy; Yuliawati, Agustina Nila; Lestari, Gusti Ayu Dewi; Andaresta, Ni Luh Putu Silvia (Jurnal Ilmu Kesehatan, 2023)
Hemodialysis (HD) in its implementation is reported to cause complications. Complications may cause the patients to receive >3 types of drugs and decrease their medication adherence. This study aimed to analyze the association between the number of complications and the number of drugs, and the association between the number of drugs with medication adherence in End-Stage Renal Disease (ESRD) patients. This research was conducted at the private hospital Denpasar in March-May 2021 with a cross-sectional design involving 93 respondents. The purposive sampling technique was used according to inclusion criteria (ESRD patients with complications, undergoing HD at least twice a week, signing informed consent) and exclusion criteria (having poor or unstable health, unable to communicate well). The research instrument used was a questionnaire (ESRD-AQ). The Mann-Whitney test and Kendall tau-b test were used to analyze the association in this study. The results showed that the majority of patients were <65 years old (83.9%), male (66.7%), 35.5% high school education, still working (51.6%), and long of diagnosed with ESRD <5 years (77%). The average patient had ≥2 complications (81.72%) and 80.64% received 1-6 types of drugs with high levels of medication adherence (67.74%). There was an association between the number of complications and the number of drugs (p=0.026) and the association between the number of drugs and medication adherence (p=0.023) with a weak correlation (r=-0,227). This indicates that complications can affect the number of drugs consumed and indirectly also affect the medication adherence of ESRD patients.